Corrosion Behavior of Reinforcing Steel Embedded in Concrete Produced with Finely Ground Pumice and Silica Fume - Keleştemur, Oğuzhan; Demirel, Bahar (My University, 2010)
In this study, the mechanical and physical properties of concrete specimens obtained by substituting cement with finely ground pumice (FGP) at proportions of 5%, 10%, 15% and 20% by weight has been investigated, in addition to analyzing the corrosion behavior of reinforcing steels embedded in these specimens. Besides, with the purpose of determining the effect of silica fume (SF) additive over the corrosion of reinforcing steels embedded in concrete with FGP, SF has been entrained to all series with the exception of the control specimen, such that it would replace with cement 10% by weight. Corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of reinforcing steels embedded in the concrete specimens was measured every day for a period of 160 days based on the ASTM C 876 standard. In the second stage, the anodic and cathodic polarization values of the steels were obtained and subsequently the corrosion currents were determined with the aid of cathodic polarization curves. In the study, it was observed that a decrease in the mechanical strength of the specimens and an increase in the corrosion rate of the reinforcing steel had taken place as a result of the FGP addition. However, it was determined that with the addition of SF into concretes supplemented with FGP, the corrosion rate of the reinforcing steel has significantly decreased.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Concrete; Corrosion; Finely ground pumice; Silica fume; Reinforcing steel